Reliable monitoring of respiratory function with home spirometry in people living with amyotrophic lateral sclerosis - Peller, Julián; Trevisan, Marcos A.; Bujia, Gaston; Aguirre, Felipe; Shalom, Diego E.; Taitz, Alan; Henze, Stephanie; Bastola, Silviya; Osik, Jason; Shewcraft, Ryan A.; Jiang, Peng; Schwartz, Joel; et al. (Frontiers in Neurology, 2025)
IntroductionMonitoring respiratory function is essential for assessing the progression of Amyotrophic Lateral Sclerosis (ALS) and planning interventions. Remote pulmonary function testing offers a promising alternative to in-clinic visits by reducing participant burden and enabling more frequent and accessible measurements.MethodsTo evaluate the feasibility and reliability of home-based spirometry in ALS, we built on the Radcliff Study, a fully remote, longitudinal, exploratory study conducted at home by 67 people with ALS (pALS). After an initial training period, participants managed their coaching autonomously, performing spirometry independently or requesting assistance from trained personnel.ResultsWe demonstrate that combining flexible coaching with a predefined automatic quality control protocol yields consistent and reliable spirometry results for tracking respiratory function over time. This approach reveals that home-measured Slow Vital Capacity (SVC) and Forced Vital Capacity (FVC) evolve similarly and follow a linear trajectory throughout the study period (7.7 ± 4.0 months), in both slow and fast progressor subpopulations.DiscussionThe observed linearity in respiratory trajectories supports the potential for early and accurate estimation of progression, reinforcing the feasibility of less frequent monitoring without compromising assessment precision and reducing the burden on both pALS and the healthcare system. Furthermore, our results align with reported in-clinic pulmonary tests, validating remote monitoring as a means to promote more equitable and accessible clinical trial designs.